Histological changes and protective effect of pipali (Piper longum) in arsenic intoxicated cockerels - SAJAN, RAM; SINGH, S P; VARMA, RACHNA; CHOUDHARY, G K; PRAKASH, ATUL (The Indian Journal of Animal Sciences, 2010)
The toxic effects of arsenic on the visceral organs of cockerel and protective effect of pipali (Piper longum) were evaluated in this study. Male White Leghorn chicks were divided randomly and equally into group 1(control), 2(arsenic 50 ppm), 3 (arsenic 100 ppm), 4 (arsenic 50 ppm + pipali 100ppm) and 5 (arsenic 100 ppm + pipali 100ppm). The experimental birds were kept in deep litter system of housing and maintained on grower ration. Birds were sacrificed after completion of 12 weeks feeding trial. At the time of necropsy organs such as liver, spleen, kidney, intestine and bursa were examined for the presence of pathological lesion. Histopathological examination reveals haemorrhages and infiltration of mononuclear cells in intestine, hydropic degeneration of hepatocytes and congestion, degeneration, necrosis, haemorrhages and infiltration of mononuclear cells in hepatic cord. Oedema, congestion, hemorrhage and infiltration of inflammatory cells in lung and degeneration of renal tubular epithelium were observed in dose dependent manner in the cockerels fed on arsenic containing feed for 12 weeks. Histopathological changes were not observed in control group as well as in pipali + arsenic fed cockerels. It is concluded from the present study that the pipali produced protective effect in arsenic induced histopulmonary and renal histopathological changes in poultry.